Flame-retardant automotive interior filler and preparation method thereof
The automobile is solved by using a sandwich structure of glueless cotton, upright cotton and mesh base cloth in the car interior filling, combining nanodiatomaceous earth/hexaphenoxycyclotriphosphazene and nanoalumina/titanium dioxide composite materials The problems of poor breathability and insufficient flame retardant performance of the interior filler have achieved high breathability, durability and excellent flame retardant performance of the interior filler.
Patent Information
- Application Number
- CN202411572326.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing car interior fillers have poor breathability and low durability, and are insufficient flame retardant in fire situations, affecting passenger safety.
Using a fiber composite of sandwich structure composed of glueless cotton, upright cotton and mesh base cloth, combined with nanodiatomaceous earth/hexaphenoxycyclotriphosphazene composite flame retardant and nanoalumina/titanium dioxide composite material, through A specific preparation method is used to prepare flame retardant polyester fibers to form an automotive interior filler with excellent breathability, durability and flame retardant properties.
It achieves high breathability, durability and excellent flame retardant properties of the car interior filler, which can slow down the spread of fire in the event of fire, improve passenger escape time, and maintain structural stability and comfort during long-term use.
Smart Images

Figure CN119217830A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile interior filling materials, and in particular to a flame retardant automobile interior filling material and a preparation method thereof. Background Art
[0002] Automotive interior fillers are an important part of building the interior environment of a car. They play a key role in appearance, practicality and durability. These fillers are usually used in the manufacture of door interior panels, ceilings, seat cushions, floor mats and other parts.
[0003] Among them, seat filling is an important component of automobile interior. It is usually composed of multiple layers of materials, including base materials (such as springs, wire mesh or hard foam), middle layers (such as soft foam) and surface materials (such as fabric, leather or artificial leather). These materials together provide the comfort, support and durability of the seat. However, for current seat fillings, the use of a large amount of foam materials will result in relatively poor air permeability. Long-term use may cause passengers to feel stuffy and uncomfortable. At the same time, due to the low strength of the material, it is easy to wear and even crack after long-term use, thus affecting the durability of the seat. In view of this, it is very necessary to develop a car interior filling that is breathable and durable.
[0004] In addition, cars are an essential means of transportation for modern people. While pursuing comfort and aesthetics, people are also paying more and more attention to the safety of cars. Therefore, the flame retardant properties of car interior materials are becoming increasingly demanding. Therefore, if the car interior filler has excellent flame retardant properties, once a fire occurs, the flame retardant filler can slow down the spread of the fire, which can buy more escape time for passengers. In addition, the flame retardant filler can quickly extinguish itself when burning, and will not form a large area of combustion, thereby reducing the damage to passengers caused by the fire. Summary of the invention
[0005] The object of the present invention is to provide a flame retardant automobile interior filler and a preparation method thereof. The flame retardant automobile interior filler has good air permeability and durability and also has excellent flame retardant properties.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A flame retardant automobile interior filler comprises a surface layer, a bottom layer and an intermediate structural layer between the surface layer and the bottom layer; the surface layer is glue-free cotton, the intermediate structural layer is upright cotton, and the bottom layer is a mesh base fabric.
[0007] The flame-retardant automobile interior filler of the present invention is a fiber composite with a sandwich structure composed of a surface layer, an intermediate structural layer, and a bottom layer, wherein the surface layer is glue-free cotton, the intermediate structural layer is 3D upright cotton, and the bottom layer is a mesh base fabric. The glue-free cotton, upright cotton, and mesh base fabric all have excellent air permeability, so the automobile interior filler prepared by the combination also has excellent air permeability.
[0008] In addition, the upright cotton as the main structural layer has good resilience and is not easy to deform. At the same time, the fiber structure in the upright cotton is compact and orderly, which can maintain a stable shape and performance for a long time. This orderly structure helps to prevent the spread of flames, and when burning, the fiber structure can quickly form a protective layer to isolate air and heat, thereby slowing down the spread of the fire. The glue-free cotton as the surface layer is soft and comfortable, with high strength. When the automotive interior filler is used to prepare automotive seats and other parts, the comfort of the seats and other parts is well guaranteed, and it is durable and not easy to be damaged. As the bottom mesh base fabric, it can effectively enhance the overall structural strength of the flame-retardant automotive interior filler, so that the filler can withstand greater pressure or tension and is not easily torn and damaged.
[0009] Preferably, the raw materials of the non-glue cotton include the following raw materials in weight percentage: 50-70% flame-retardant polyester staple fiber, 30-50% low melting point fiber; The raw materials of the upright cotton include the following raw materials in percentage by weight: 75-85% of flame-retardant polyester fiber and 15-25% of low-melting-point fiber.
[0010] The raw material of the mesh base fabric includes flame-retardant polyester filaments.
[0011] Preferably, the flame-retardant polyester staple fiber, flame-retardant polyester fiber, and flame-retardant polyester filament all comprise the following raw materials in parts by weight: 100 parts of polyester chips, 10 to 15 parts of MBS resin, 8 to 12 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 0.7 to 1.2 parts of nano-alumina / titanium dioxide composite material, and 0.3 to 0.6 parts of antioxidant.
[0012] In the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant of the present invention, the nano-diatomite forms a porous isolation layer at high temperature, which can block the diffusion path of flame and thermal radiation, and can also absorb heat to slow down the spread of fire. On this basis, the added hexaphenoxy cyclotriphosphazene can promote the carbonization of polymer during the combustion process, and the phosphazene and benzene ring groups will also be further cracked to produce small molecular fragments, further promoting the formation and stabilization of the carbon layer.
[0013] The present invention adopts a nano-alumina / titanium dioxide composite material as a reinforcing material, wherein nano-titanium dioxide is dispersed in polyester, and the reinforcing phase formed by the nano-titanium dioxide improves the strength, toughness and thermal stability of the polyester. At the same time, the present invention also modifies the nano-titanium dioxide by using alumina sol, so that the surface of the nano-titanium dioxide is loaded with nano-aluminum oxide, so that the dispersibility of the nano-titanium dioxide is better and the binding force between the nano-titanium dioxide and the polyester is significantly enhanced, so that the mechanical properties of each flame-retardant polyester fiber are more excellent. And because the surface of the nano-titanium dioxide is dispersed with nano-aluminum oxide, the nano-aluminum oxide also has certain flame retardant properties, thereby further improving the flame retardant properties of the polyester fiber. At the same time, the nano-aluminum oxide / titanium dioxide composite material of the present invention has a good antibacterial effect, so that the polyester fiber exhibits excellent antibacterial properties.
[0014] Preferably, the preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone of 20-25 times of its mass, and then hexaphenoxy cyclotriphosphazene of 10-15% of the mass of the nano-diatomite and γ-glycidyloxypropyltrimethoxysilane of 1-1.5% of the mass of the nano-diatomite are added, the temperature is raised to 40-45° C. and stirred at a constant temperature for 2-3 hours, and then the acetone is removed by vacuum concentration, and the material after the acetone is removed is ground and dispersed to obtain the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant.
[0015] When preparing the composite flame retardant, the present invention adds nano diatomite, hexaphenoxy cyclotriphosphazene and an appropriate amount of gamma-glycidyloxypropyltrimethoxysilane into acetone, so that the hexaphenoxy cyclotriphosphazene is adsorbed on the nano diatomite, the nano diatomite and the hexaphenoxy cyclotriphosphazene have high mixing uniformity, and the surface of the nano diatomite has more active groups, so the bonding force between the nano diatomite and the polyester is enhanced, so that the composite flame retardant can significantly improve the flame retardant performance of the polyester without adversely affecting the mechanical properties of the polyester.
[0016] Preferably, the preparation method of the nano-alumina / titania composite material comprises the following steps: adding deionized water to a reactor, then adding nano-titanium dioxide and alumina sol, performing ultrasonic treatment while stirring for 1 to 2 hours, then sealing the reactor, evacuating to -0.09 to -0.08 MPa, maintaining for 2 to 3 hours, and drying in an electric heating blast drying oven at 85 to 90° C., then heating the obtained powder to 800 to 850° C. in a nitrogen atmosphere, and maintaining the temperature for 2 to 2.5 hours, and dispersing to obtain the nano-alumina / titania composite material; Preferably, the mass ratio of the deionized water, nano-titanium dioxide and alumina sol is 200:5-10:2-4; the particle size of the nano-titanium dioxide is 150-200 nm; the solid content of the alumina sol is 20-25%, wherein the average particle size of alumina is 30-50 nm.
[0017] Preferably, the preparation methods of the flame retardant polyester staple fibers, flame retardant polyester fibers, and flame retardant polyester filaments all comprise the following steps: Mixing 1 / 3 to 1 / 2 of the polyester chips with MBS resin, nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, nano-alumina / titanium dioxide composite material and antioxidant, and drying the mixture to obtain a dried mixture; placing the dried mixture in a twin-screw extruder for blending, melting, extruding and granulating to obtain flame-retardant polyester pellets; The remaining amount of polyester chips is dried, mixed with the flame-retardant polyester pellets, and then melt-spinned to obtain a blended flame-retardant polyester fiber with a target fineness; The flame-retardant polyester staple fibers, flame-retardant polyester fibers, and flame-retardant polyester filaments are obtained by cutting and processing blended flame-retardant polyester fibers of corresponding fineness.
[0018] Preferably, the preparation method of the non-glue cotton comprises the following steps: mixing the flame-retardant polyester staple fiber and the low-melting-point fiber and placing the mixture in an opener for opening treatment, then placing the mixture in a carding machine to card into a fiber web, then placing the mixture in a web laying machine for web laying, and then placing the mixture in a setting machine for hot pressing and setting to obtain the non-glue cotton; The preparation method of the upright cotton comprises the following steps: mixing the flame-retardant polyester fiber and the low-melting-point fiber and placing them in an opener for opening treatment, placing them in a carding machine for combing into a fiber web, and then placing the fiber web in a vertical web laying machine for vertical web laying, three-dimensionally forming and then heating and forming to obtain the upright cotton; The preparation method of the mesh base fabric comprises the following steps: warping, weaving and post-finishing the flame-retardant polyester filaments to prepare the mesh base fabric.
[0019] Preferably, the surface layer and the middle structural layer as well as the middle structural layer and the bottom layer are bonded by hot melt adhesive or connected by flame compounding.
[0020] As a general inventive concept, the present invention provides a method for preparing a flame-retardant automobile interior filler, the method comprising the following steps: firstly compounding the upper surface of a bottom layer with an intermediate structure layer by hot melt adhesive to form a double-layer structure; then compounding a side of the double-layer structure away from the bottom layer with a surface layer by hot melt adhesive to prepare the flame-retardant automobile interior filler; Or the preparation method includes the following steps: flame-compounding the upper surface of the bottom layer with the middle structural layer by a flame-compounding machine, and forming a double-layer structure after cooling; and flame-compounding the side of the double-layer structure away from the bottom layer with the surface layer by a flame-compounding machine, and preparing the flame-retardant automobile interior filler after cooling.
[0021] The beneficial effects of the present invention are: 1. The flame-retardant automobile interior filler of the present invention is prepared by combining glue-free cotton, upright cotton and mesh base fabric, so that the overall structure of the obtained interior filler is stable, the air permeability is good and it is durable, and it has good flame retardancy. The interior filler can also be widely used as a filling material in automobile interiors, seats, headrests, etc.
[0022] 2. In order to further improve the flame retardancy and strength of flame retardant automobile interior fillings, the present invention has developed a new type of blended flame retardant polyester fiber, which can be used as a raw material for preparing glue-free cotton, upright cotton, and mesh base cloth.
[0023] The flame retardant used in the flame retardant polyester fiber is a nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant. The composite flame retardant is prepared by combining nano-diatomite and hexaphenoxy cyclotriphosphazene in a specific method. Each flame retardant synergistically exerts its flame retardant advantages, which can significantly improve the flame retardant properties of the flame retardant polyester fiber without adversely affecting the mechanical properties of the polyester fiber. Compared with the use of nano-titanium dioxide, the use of nano-alumina / titanium dioxide composite materials as reinforcing agents can make the mechanical properties of flame retardant polyester fibers more excellent, thereby further improving the durability of flame retardant automotive interior fillers. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a schematic structural diagram of the flame retardant automobile interior trim filler of the present invention; In the figure: 1, bottom layer; 2, middle structural layer; 3, surface layer. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1: A flame retardant automotive interior filler, such as Figure 1 As shown, it includes a surface layer 3, a bottom layer 1 and an intermediate structure layer 2 located between the surface layer 3 and the bottom layer 1; the surface layer 3 and the intermediate structure layer 2 as well as the intermediate structure layer 2 and the bottom layer 1 are bonded by hot melt adhesive.
[0028] The surface layer 3 is glue-free cotton, the middle structural layer 2 is upright cotton, and the bottom layer 1 is a mesh base fabric.
[0029] The raw materials of the non-glue cotton include the following raw materials in weight percentage: 60% flame-retardant polyester staple fiber and 4080 low-melting-point fiber; the raw materials of the upright cotton include the following raw materials in weight percentage: 80% flame-retardant polyester fiber and 20% 4080 low-melting-point fiber. The raw materials of the mesh base fabric include flame-retardant polyester filament.
[0030] In this embodiment, the flame-retardant polyester staple fiber, flame-retardant polyester fiber, and flame-retardant polyester filament all include the following raw materials in parts by weight: 100 parts of polyester chips, 13 parts of MBS resin, 10 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 1.1 parts of nano-alumina / titanium dioxide composite material, and 0.5 parts of antioxidant 1010.
[0031] The preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant in this embodiment comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone 25 times its mass, and then 14% of hexaphenoxycyclotriphosphazene by mass of the nano-diatomite and 1.5% of γ-glycidyloxypropyltrimethoxysilane by mass of the nano-diatomite are added, the temperature is raised to 42°C and stirred at a constant temperature for 3 hours, and then the acetone is removed by vacuum concentration, and the material after the acetone is removed is ground and dispersed to obtain a nano-diatomite / hexaphenoxycyclotriphosphazene composite flame retardant.
[0032] The preparation method of the nano-alumina / titania composite material in this embodiment includes the following steps: adding deionized water to a reactor, then adding nano-titania and alumina sol, performing ultrasonic treatment for 1.5 hours while stirring, then sealing the reactor, evacuating to -0.09MPa, maintaining for 2.5 hours, and then drying in an electric blast drying oven at 90°C, then heating the obtained powder to 820°C under a nitrogen atmosphere and keeping it warm for 2.5 hours, and dispersing to obtain the nano-alumina / titania composite material; wherein the mass ratio of deionized water, nano-titania, and alumina sol is 200:9:3; the particle size of nano-titania is 150~200nm; the solid content of alumina sol is 20%, wherein the average particle size of alumina is 30nm.
[0033] The preparation methods of the flame-retardant polyester staple fibers, flame-retardant polyester fibers, and flame-retardant polyester filaments in this embodiment all include the following steps: 1 / 3 of the polyester chips are mixed with MBS resin, nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, nano-alumina / titanium dioxide composite material, and antioxidant, and then dried to obtain a dried mixture; the dried mixture is placed in a twin-screw extruder for blending, melt extrusion and granulation to obtain flame-retardant polyester pellets; the remaining amount of polyester chips is dried, mixed with the flame-retardant polyester pellets, and then melt-spun to obtain a blended flame-retardant polyester fiber of target fineness; In this embodiment, the flame-retardant polyester staple fibers, flame-retardant polyester fibers, and flame-retardant polyester filaments are obtained by cutting and processing blended flame-retardant polyester fibers of corresponding fineness.
[0034] In this embodiment, the preparation method of the non-glue cotton comprises the following steps: the flame-retardant polyester staple fiber and the 4080 low-melting-point fiber are mixed and placed in an opener for opening treatment, then placed in a carding machine for carding into a fiber web, then laid by a web laying machine, and then sent to a setting machine for hot pressing and setting to obtain the non-glue cotton; The preparation method of upright cotton comprises the following steps: mixing flame-retardant polyester fiber and 4080 low-melting-point fiber and placing the mixture in an opener for opening treatment, placing the mixture in a carding machine for combing into a fiber web, and then placing the fiber web in a vertical web laying machine for vertical web laying, three-dimensionally forming the mixture and then heating the mixture to obtain upright cotton; The preparation method of the mesh base fabric comprises the following steps: warping, weaving and post-finishing the flame-retardant polyester filaments to prepare the mesh base fabric.
[0035] The method for preparing the flame-retardant automobile interior filler in this embodiment includes the following steps: first, the upper surface of the bottom layer 1 is compounded with the middle structure layer 2 by hot melt adhesive to form a double-layer structure; then, the side of the double-layer structure away from the bottom layer 1 is compounded with the surface layer 3 by hot melt adhesive to prepare the flame-retardant automobile interior filler.
[0036] Embodiment 2: A flame retardant automobile interior filling material, which is different from Example 1 in that the surface layer 3 and the middle structure layer 2 as well as the middle structure layer 2 and the bottom layer 1 are connected by flame composite.
[0037] The raw materials of the non-glue cotton include the following raw materials in weight percentage: 50% flame-retardant polyester staple fiber and 50% 4080 low-melting-point fiber; the raw materials of the upright cotton include the following raw materials in weight percentage: 78% flame-retardant polyester fiber and 22% 4080 low-melting-point fiber. The raw materials of the mesh base fabric include flame-retardant polyester filament.
[0038] In this embodiment, the flame-retardant polyester staple fiber, flame-retardant polyester fiber, and flame-retardant polyester filament all include the following raw materials in parts by weight: 100 parts of polyester chips, 12 parts of MBS resin, 12 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 0.7 parts of nano-alumina / titanium dioxide composite material, and 0.3 parts of antioxidant 1010.
[0039] The preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant in this embodiment comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone 25 times its mass, and then 15% of the mass of the nano-diatomite hexaphenoxy cyclotriphosphazene and 1.5% of the mass of the nano-diatomite γ-glycidyloxypropyltrimethoxysilane are added, the temperature is raised to 45°C and stirred at a constant temperature for 3 hours, and then the acetone is removed by vacuum concentration, and the material after the acetone is removed is ground and dispersed to obtain a nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant.
[0040] The preparation method of the nano-alumina / titania composite material in this embodiment includes the following steps: adding deionized water to a reactor, then adding nano-titanium dioxide and alumina sol, performing ultrasonic treatment for 2 hours while stirring, then sealing the reactor, evacuating to -0.09MPa, maintaining for 3 hours, and then drying in an electric blast drying oven at 85°C, then heating the obtained powder to 850°C under a nitrogen atmosphere and keeping it warm for 2.5 hours to obtain a nano-alumina / titania composite material after dispersion; wherein the mass ratio of deionized water, nano-titanium dioxide and alumina sol is 200:10:3; the particle size of the nano-titanium dioxide is 150~200nm; the solid content of the alumina sol is 25%, and the average particle size of alumina is 50nm.
[0041] The method for preparing the flame-retardant automobile interior filler in this embodiment includes the following steps: flame-compounding the upper surface of the bottom layer 1 with the middle structure layer 2 by a flame laminating machine, and forming a double-layer structure after cooling; and flame-compounding the side of the double-layer structure away from the bottom layer 1 with the surface layer 3 by a flame laminating machine, and preparing the flame-retardant automobile interior filler after cooling.
[0042] Embodiment 3: A flame retardant automotive interior filler, which is different from Example 1 in that the raw materials of the non-glue cotton include the following raw materials in weight percentage: 55% flame retardant polyester staple fiber and 45% 4080 low melting point fiber; the raw materials of the upright cotton include the following raw materials in weight percentage: 85% flame retardant polyester fiber and 15% 4080 low melting point fiber. The raw materials of the mesh base fabric include flame retardant polyester filaments.
[0043] In this embodiment, the flame-retardant polyester staple fiber, flame-retardant polyester fiber, and flame-retardant polyester filament all include the following raw materials in parts by weight: 100 parts of polyester chips, 10 parts of MBS resin, 10 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 1.2 parts of nano-alumina / titanium dioxide composite material, and 0.5 parts of antioxidant 1010.
[0044] The preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant in this embodiment comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone 20 times the mass of the nano-diatomite, and then hexaphenoxy cyclotriphosphazene (12% by mass of the nano-diatomite) and γ-glycidyloxypropyltrimethoxysilane (1% by mass of the nano-diatomite) are added, the temperature is raised to 45° C. and stirred at a constant temperature for 2 hours, and then the acetone is removed by reduced pressure concentration, and the material after the acetone is removed is ground and dispersed to obtain the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant.
[0045] The preparation method of the nano-alumina / titania composite material in this embodiment includes the following steps: adding deionized water to a reactor, then adding nano-titania and alumina sol, performing ultrasonic treatment while stirring for 1 hour, then sealing the reactor, evacuating to -0.08MPa, maintaining for 2 hours, and then drying in an electric blast drying oven at 90°C, then heating the obtained powder to 850°C under a nitrogen atmosphere and keeping it warm for 2 hours, and dispersing to obtain the nano-alumina / titania composite material; wherein the mass ratio of deionized water, nano-titania, and alumina sol is 200:8:2; the particle size of nano-titania is 150~200nm; the solid content of the alumina sol is 25%, wherein the average particle size of alumina is 50nm.
[0046] Embodiment 4: A flame retardant automobile interior filling material, which is different from Example 1 in that the surface layer 3 and the middle structure layer 2 as well as the middle structure layer 2 and the bottom layer 1 are connected by flame composite.
[0047] The raw materials of the non-glue cotton include the following raw materials in weight percentage: 70% flame-retardant polyester staple fiber and 30% 4080 low-melting-point fiber; the raw materials of the upright cotton include the following raw materials in weight percentage: 75% flame-retardant polyester fiber and 25% 4080 low-melting-point fiber. The raw materials of the mesh base fabric include flame-retardant polyester filament.
[0048] In this embodiment, the flame-retardant polyester staple fiber, flame-retardant polyester fiber, and flame-retardant polyester filament all include the following raw materials in parts by weight: 100 parts of polyester chips, 15 parts of MBS resin, 8 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 1 part of nano-alumina / titanium dioxide composite material, and 0.6 parts of antioxidant.
[0049] The preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant in this embodiment comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone 20 times the mass of the nano-diatomite, and then hexaphenoxy cyclotriphosphazene (10% by mass of the nano-diatomite) and γ-glycidyloxypropyltrimethoxysilane (1.2% by mass of the nano-diatomite) are added, the temperature is raised to 40° C. and stirred at a constant temperature for 2.5 hours, and then the acetone is removed by reduced pressure concentration, and the material after the acetone is removed is ground and dispersed to obtain the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant.
[0050] The preparation method of the nano-alumina / titania composite material in this embodiment includes the following steps: adding deionized water to a reactor, then adding nano-titania and alumina sol, performing ultrasonic treatment for 1.5 hours while stirring, then sealing the reactor, evacuating to -0.08MPa, maintaining for 3 hours, and then drying in an electric blast drying oven at 90°C, then heating the obtained powder to 800°C under a nitrogen atmosphere and keeping it warm for 2.5 hours, and dispersing to obtain the nano-alumina / titania composite material; wherein the mass ratio of deionized water, nano-titania, and alumina sol is 200:5:4; the particle size of the nano-titania is 150~200nm; the solid content of the alumina sol is 20%, wherein the average particle size of alumina is 30nm.
[0051] The method for preparing the flame-retardant automobile interior filler in this embodiment includes the following steps: flame-compounding the upper surface of the bottom layer 1 with the middle structure layer 2 by a flame laminating machine, and forming a double-layer structure after cooling; and flame-compounding the side of the double-layer structure away from the bottom layer 1 with the surface layer 3 by a flame laminating machine, and preparing the flame-retardant automobile interior filler after cooling.
[0052] Comparative Example 1: The difference from Example 4 is that the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant is replaced by a mixture of nano-diatomite and hexaphenoxy cyclotriphosphazene in a mass ratio of 1:0.1.
[0053] Comparative Example 2: The difference from Example 4 is that the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant is replaced by a mixture of nano-diatomite and hexaphenoxy cyclotriphosphazene in a mass ratio of 1:1.
[0054] Comparative Example 3: The difference from Example 4 is that the nano-alumina / titania composite material is replaced by nano-titania.
[0055] Performance Test: 1. For the flame-retardant polyester fiber materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3, the limiting oxygen index test was carried out according to the method in GB / T 2406.2-2009, and the vertical burning level test was carried out according to the method in GB / T 2408-2008. The specific test results are shown in Table 1.
[0056] Table 1: Limiting oxygen index / % Vertical burning level Example 1 37.6 V-0 Example 2 39.4 V-0 Example 3 38.9 V-0 Example 4 38.0 V-0 Comparative Example 1 34.0 V-0 Comparative Example 2 38.6 V-0 Comparative Example 3 37.6 V-0 It can be seen from Table 1 that the flame retardant polyester fibers prepared in Examples 1-4 of the present invention have excellent flame retardant properties. It can be seen from the comparison between Example 4 and Comparative Example 1 that if the method of the present invention is not used to compound the nano-diatomaceous earth and the hexaphenoxy cyclotriphosphazene composite flame retardant, the flame retardant properties will decrease. It can be seen from Comparative Examples 1 and 2 that when the amount of hexaphenoxy cyclotriphosphazene added increases, the flame retardant properties will increase, but it can be seen from subsequent tests that the mechanical properties will be significantly reduced.
[0057] 2. According to the methods of Examples 1 to 4 and Comparative Examples 1 to 3, a blended flame-retardant polyester fiber with a fineness of 5 dtex was prepared, and the breaking strength and breaking elongation were tested according to GB / T 14337-2008, and the moisture regain was tested according to GB / T 3503-2008. The specific test results are shown in Table 2.
[0058] Table 2: Breaking strength / (cN / dtex) Elongation at break / / % Moisture regain / % Example 1 6.02 42.2 0.25 Example 2 5.93 40.6 0.27 Example 3 6.06 41.7 0.24 Example 4 6.17 43.7 0.29 Comparative Example 1 5.32 35.8 0.32 Comparative Example 2 4.10 27.5 0.34 Comparative Example 3 5.42 37.1 0.29 As shown in Table 2, the flame-retardant polyester fiber prepared by the method of Examples 1 to 4 of the present invention has high breaking strength and elongation at break, high overall strength and good toughness, which can make the flame-retardant automotive interior filler not easily damaged by external forces, and low moisture regain, which is conducive to the flame-retardant automotive interior filler maintaining its comfort. As shown in Example 4 and Comparative Examples 1 to 2, when the composition and preparation method of the flame retardant are different, the mechanical properties of the flame-retardant polyester fiber will also be significantly reduced. As shown in Example 4 and Comparative Example 3, if the nano titanium dioxide is not modified accordingly, the strength of the flame-retardant polyester fiber will be reduced.
[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A flame retardant automobile interior filler, characterized in that: The flame retardant automobile interior filling material comprises a surface layer, a bottom layer and an intermediate structural layer located between the surface layer and the bottom layer; the surface layer is glue-free cotton, the intermediate structural layer is upright cotton, and the bottom layer is a mesh base fabric.
2. The flame retardant automobile interior filler according to claim 1, characterized in that: The raw materials of the non-glue cotton include the following raw materials in weight percentage: 50-70% flame-retardant polyester staple fiber and 30-50% low-melting point fiber; The raw materials of the upright cotton include the following raw materials in weight percentage: 75-85% flame-retardant polyester fiber and 15-25% low-melting point fiber; The raw material of the mesh base fabric includes flame-retardant polyester filaments.
3. The flame retardant automobile interior filler according to claim 2, characterized in that: The flame-retardant polyester staple fiber, flame-retardant polyester fiber and flame-retardant polyester filament all include the following raw materials in parts by weight: 100 parts of polyester chips, 10-15 parts of MBS resin, 8-12 parts of nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, 0.7-1.2 parts of nano-alumina / titanium dioxide composite material and 0.3-0.6 parts of antioxidant.
4. The flame retardant automobile interior filler according to claim 3, characterized in that: The preparation method of the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant comprises the following steps: Nano-diatomite with a particle size of 200-300 nm is dispersed in acetone of 20-25 times of its mass, and then hexaphenoxy cyclotriphosphazene of 10-15% of the mass of the nano-diatomite and γ-glycidyloxypropyltrimethoxysilane of 1-1.5% of the mass of the nano-diatomite are added, the temperature is raised to 40-45° C. and stirred at a constant temperature for 2-3 hours, and then the acetone is removed by vacuum concentration, and the material after the acetone is removed is ground and dispersed to obtain the nano-diatomite / hexaphenoxy cyclotriphosphazene composite flame retardant.
5. The flame retardant automobile interior filler according to claim 3, characterized in that: The preparation method of the nano-alumina / titania composite material comprises the following steps: adding deionized water into a reactor, then adding nano-titania and alumina sol, performing ultrasonic treatment for 1-2 hours while stirring, then sealing the reactor, evacuating to -0.09-0.08MPa, maintaining for 2-3 hours, and then drying in an electric heated blast drying oven at 85-90°C, then heating the obtained powder to 800-850°C in a nitrogen atmosphere, and maintaining the temperature for 2-2.5 hours, and dispersing to obtain the nano-alumina / titania composite material.
6. The flame retardant automobile interior filler according to claim 5, characterized in that: The mass ratio of deionized water, nano titanium dioxide and alumina sol is 200:5-10:2-4; the particle size of the nano titanium dioxide is 150-200nm; the solid content of the alumina sol is 20-25%, wherein the average particle size of alumina is 30-50nm.
7. The flame retardant automobile interior filler according to claim 3, characterized in that: The preparation methods of the flame-retardant polyester staple fibers, flame-retardant polyester fibers, and flame-retardant polyester filaments all comprise the following steps: 1 / 3 to 1 / 2 of the polyester chips are mixed with MBS resin, nano-diatomaceous earth / hexaphenoxy cyclotriphosphazene composite flame retardant, nano-alumina / titanium dioxide composite material, and antioxidant, and then dried to obtain a dried mixture; the dried mixture is placed in a twin-screw extruder for blending, melt extrusion and granulation to obtain flame-retardant polyester pellets; the remaining amount of polyester chips is dried, mixed with the flame-retardant polyester pellets, and then melt-spinned to obtain a blended flame-retardant polyester fiber of target fineness; The flame-retardant polyester staple fibers, flame-retardant polyester fibers, and flame-retardant polyester filaments are obtained by cutting and processing blended flame-retardant polyester fibers of corresponding fineness.
8. The method for preparing a flame retardant automobile interior filling material according to claim 2, characterized in that: The preparation method of the non-glue cotton comprises the following steps: mixing the flame-retardant polyester staple fiber and the low-melting-point fiber and placing them in an opener for opening treatment, placing them in a carding machine for carding into a fiber web, and then placing them in a web laying machine for web laying, and then placing them in a setting machine for hot pressing and setting to obtain the non-glue cotton; The preparation method of the upright cotton comprises the following steps: mixing the flame-retardant polyester fiber and the low-melting-point fiber and placing them in an opener for opening treatment, placing them in a carding machine for combing into a fiber web, and then placing the fiber web in a vertical web laying machine for vertical web laying, three-dimensionally forming and then heating and forming to obtain the upright cotton; The preparation method of the mesh base fabric comprises the following steps: warping, weaving and post-finishing the flame-retardant polyester filaments to prepare the mesh base fabric.
9. The flame retardant automobile interior filler according to claim 1, characterized in that: The surface layer and the middle structure layer as well as the middle structure layer and the bottom layer are bonded by hot melt adhesive or connected by flame compounding.
10. A method for preparing a flame retardant automotive interior filler according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: firstly, the upper surface of the bottom layer is compounded with the middle structure layer by hot melt adhesive to form a double-layer structure; then, the side of the double-layer structure away from the bottom layer is compounded with the surface layer by hot melt adhesive to prepare the flame-retardant automobile interior filler; Or the preparation method includes the following steps: flame-compounding the upper surface of the bottom layer with the middle structural layer by a flame-compounding machine, and forming a double-layer structure after cooling; and flame-compounding the side of the double-layer structure away from the bottom layer with the surface layer by a flame-compounding machine, and preparing the flame-retardant automobile interior filler after cooling.
Citation Information
Patent Citations
Negative ion flame-retardant anti-bacterial fiber and preparation method thereof
CN101586267A
Oil-resistant corrosion-resistant sealing washer sizing material used for offshore oil platform and preparation method thereof
CN104927364A
Automobile instrument socket and preparation method thereof
CN106589772A
High-performance automotive acoustic cotton and manufacturing process thereof
CN114182434A
Flame-retardant color master batch and preparation method thereof
CN116769244A